Solvency capital requirement for German unit-linked insurance products - Michael Kochanski (German Risk and Insurance Review (GRIR), 2010)
Innovative Lebensversicherungsprodukte wie fondsgebundene Lebensversicherungen, Hybrid-Lebensversicherungen und Variable Annuities erfreuen sich rasch zunehmender Nachfrage und haben einen großen Anteil am Neugeschäft in Deutschland. Da traditionelle Versicherungsprodukte weiterhin den Großteil an den Beständen der Lebensversicherer ausmachen, konzentrierte sich die Diskussion über die Standardformel zur Berechnung des Solvenzkapitals bisher weitgehend auf ebendiese Produkte. Eine ausführliche Diskussion darüber, wie Solvenzkapital für innovative Lebensversicherungsprodukte im Rahmen der Standardformel berechnet werden kann, ist deshalb erforderlich. – – Innovative life insurance products such as unit-linked life insurance, hybrid life insurance, and variable annuities are rapidly gaining popularity and becoming a major part of new business in Germany. However, since traditional life insurance products still dominate the portfolios of life insurance companies, discussions about the standard formula for determining the solvency capital requirement have focused on this type of business. Any detailed discussion on how to calculate the solvency capital requirement for innovative life insurance products within the standard formula has yet to occur. This paper brings to light some interesting facts about unit-linked business and Solvency II. The modeling of lapses is another focus of research, reflecting the increased importance of lapse risks for innovative life insurance products. Since there are strong concerns about nonlinearities between the various risks, especially between market risk and lapse risk, the paper examines this problem as well. Finally, an alternative method for calculating the net solvency capital requirement, the so-called single equivalent scenario (also referred to as the killer-scenario), is presented.
Keywords: 360; FLV; Solvency II; Standardformel; single equivalent scenario; dynamisches Storno; unit-linked insurance; Solvency II; standard formula; single equivalent scenario; dynamic policyholder behavior